MAKNA DAN NILAI PEDAGOGIS-TEOLOGIS DARI LAGU “DOA AKHIR TAHUN” KARYA DAUD SALEH LUJI - Daud Saleh Luji (Institut Agama Kristen Negeri Kupang, 2022)
The purpose of this research is to find out the pedagogical-theological value of the song